A hydrogel thin layer-foam-based solar evaporator and its preparation method and application
Patent Information
- Application Number
- CN202411729784.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-11-29
AI Technical Summary
The preparation process of existing solar interface evaporators is complicated and time-consuming, and the evaporation rate and energy utilization efficiency are low, making it difficult to show excellent salt resistance in complex water samples.
The hydrogel thin layer-foam-based solar evaporator is quickly prepared by spraying, using carbon-based indium material as the photothermal layer, and polyvinyl alcohol and glutaraldehyde are added to the hydrogel thin layer to form an efficient evaporation system.
A simplified preparation process is achieved, which significantly improves the evaporation rate and energy utilization efficiency, and exhibits excellent salt resistance and high evaporation rate in high salt and wastewater.
Smart Images

Figure CN119215438B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of water treatment, and in particular relates to a hydrogel thin layer-foam-based solar evaporator and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Solar interfacial evaporation technology uses green and renewable solar energy as an energy source. The local heat generated at the gas-liquid interface induces water evaporation, reduces energy loss, and improves steam generation efficiency. It is environmentally friendly and pollution-free during operation, and is low-cost. It has gradually become a popular water treatment method. In the interfacial solar evaporation system, the research direction is mainly focused on the adjustment of the water transfer path, which is used to improve the evaporation rate and energy utilization efficiency of the interfacial evaporation system. However, the preparation process of the general evaporator is complicated and time-consuming. For example, the three-dimensional porous hydrogel evaporator with a conical cavity needs to be freeze-dried and repeatedly operated at a low temperature; a polymer foam evaporator covalently linked to an aniline oligomer and a hydrophilic polyethylene glycol requires an additional 0.3mm needle to pierce the polymer evaporator. Artificial pores increase the difficulty of evaporator preparation to a certain extent. Therefore, how to provide an evaporator with a simple preparation process and a high evaporation rate is a technical problem that needs to be solved urgently. Summary of the invention
[0004] In order to solve the deficiencies of the prior art, the purpose of the present invention is to provide a hydrogel thin layer-foam-based solar evaporator and its preparation method and application. The present invention quickly prepares a foam-based evaporator loaded with a hydrogel thin layer by a simple spraying method. The preparation process is simple, and the excellent hydrophilicity of the evaporator as a whole can achieve ideal water transport, reduce the binding energy of water molecules, significantly reduce the evaporation enthalpy, and have good evaporation rate and energy utilization efficiency. In addition, the evaporator also exhibits excellent salt resistance in 3.5-20wt.% brine, and a higher evaporation rate in acid, alkali and various dye wastewater, which exceeds most advanced evaporators.
[0005] In order to achieve the above object, the technical solution of the present invention is:
[0006] In a first aspect, the present invention provides a hydrogel thin layer-foam-based solar evaporator, comprising a foam substrate, a photothermal layer and a hydrogel thin layer; the photothermal layer and the hydrogel thin layer are sequentially coated on the foam substrate to form an FCH evaporator; wherein the photothermal layer is a carbon-based indium material.
[0007] The photothermal layer can efficiently convert solar energy into thermal energy, which is used to heat body water to generate water vapor. The precisely designed capillary water channels in the hydrogel layer can enhance the water transport capacity, reduce the binding energy of water molecules, and significantly reduce the evaporation enthalpy to achieve efficient and rapid water evaporation.
[0008] In one or more embodiments, a photothermal layer is coated on the hydrogel thin layer to form a FCHC evaporator.
[0009] In one or more embodiments, the foam substrate is melamine foam or polyurethane foam, preferably melamine foam. Melamine foam or polyurethane foam, which have a porous structure and a hydrophilic foam surface, can achieve the evaporation effect of the present invention, while other foams such as polyethylene foam, polystyrene foam, and polypropylene foam, which have a hydrophobic foam surface, cannot achieve effective evaporation.
[0010] The average pore size of the foam is 40-60 μm, preferably 50 μm.
[0011] In one or more embodiments, the carbon-based indium material is obtained by mixing an indium nitrate solution and a trimesic acid solution, preparing a precursor by a hydrothermal method, and calcining the precursor under a protective atmosphere.
[0012] In one or more embodiments, the hydrogel thin layer includes a carbon-based indium material, polyvinyl alcohol and glutaraldehyde.
[0013] In a second aspect, the present invention provides a method for preparing the above-mentioned hydrogel thin layer-foam-based solar evaporator, comprising:
[0014] (1) Assembling the foam substrate into a Foam evaporator (foam evaporator);
[0015] (2) coating the carbon-based indium material aqueous solution on the inner and outer surfaces of the foam substrate to obtain an FC evaporator;
[0016] (3) A carbon-based indium material, polyvinyl alcohol and glutaraldehyde are mixed and coated on the inner and outer surfaces of a foam substrate to obtain a FCH evaporator.
[0017] In one or more embodiments, the step (4) is further included, coating the inner and outer surfaces of the FCH evaporator with an aqueous solution of a carbon-based indium material to obtain a FCHC evaporator.
[0018] In one or more embodiments, the length, width and thickness of the evaporation interface are not particularly limited and can be selected according to actual needs. In the embodiment of the present invention, the length, width and thickness are 8 cm×4 cm×0.5 cm respectively.
[0019] In one or more embodiments, before step (1), the foam substrate is further washed and dried. Specifically, the foam substrate is washed with water and ethanol several times to remove dust and grease on the surface.
[0020] In one or more embodiments, in the step (1), the foam substrate is melamine foam or polyurethane foam.
[0021] In one or more embodiments, in step (2), the concentration of the carbon-based indium material aqueous solution is 0.05-1 g / mL, preferably 0.05-0.1 g / mL.
[0022] In one or more embodiments, in step (3), the carbon-based indium material and polyvinyl alcohol are mixed to form solution C, and solution C and glutaraldehyde are sequentially coated on the inner and outer surfaces of the foam substrate. Specifically, solution C is first sprayed on the inner and outer surfaces of the foam substrate; then a layer of glutaraldehyde (GA) is sprayed on the inner and outer surfaces of the foam substrate for cross-linking, and finally assembled to form an FCH evaporator containing a thin layer of hydrogel.
[0023] Furthermore, the concentration of the carbon-based indium material in solution C is 0.05-1 g / mL, preferably 0.1-0.2 g / mL.
[0024] Furthermore, the mass fraction of the polyvinyl alcohol (PVA) is 10-15wt.%, preferably 12.5wt.%.
[0025] Furthermore, during coating, the volume ratio of solution C to glutaraldehyde is (9-10):1.
[0026] In one or more embodiments, in step (4), the concentration of the carbon-based indium material aqueous solution is 0.05-1 g / mL, preferably 0.05-0.1 g / mL.
[0027] The volume ratio of the coating amount of the carbon-based indium material aqueous solution in step (2), the coating amount of solution C in step (3), and the coating amount of the carbon-based indium material aqueous solution in step (4) is (1-5):(1-5):(1-3), preferably (1-3):(1-3):1.
[0028] In a third aspect, the present invention provides a carbon-based indium material, wherein the carbon-based indium material is obtained by mixing an indium nitrate solution and a trimesic acid solution, preparing a precursor by a hydrothermal method, and calcining the precursor under a protective atmosphere.
[0029] Preferably, indium nitrate is dissolved in an alcohol solution to obtain an indium nitrate solution, preferably a methanol solution.
[0030] Preferably, trimesic acid is dissolved in N,N-dimethylformamide to obtain a trimesic acid solution.
[0031] Preferably, the mass ratio of indium nitrate to trimesic acid is 1:(5-10), preferably 1:5.
[0032] Preferably, the calcination temperature is 450-550°C, and the calcination time is 1-3h, preferably 500°C, 2h.
[0033] In a fourth aspect, the present invention provides the use of the above-mentioned carbon-based indium material in the preparation of a solar evaporator.
[0034] In a fifth aspect, the present invention provides an application of a hydrogel thin layer-foam-based solar evaporator in seawater desalination, high-salt wastewater, acid-base and various dye wastewater treatment, wherein the hydrogel thin layer-foam-based solar evaporator is the above-mentioned hydrogel thin layer-foam-based solar evaporator, or is the hydrogel thin layer-foam-based solar evaporator obtained by the above-mentioned preparation method.
[0035] One or some of the above technical solutions have the following advantages or beneficial effects:
[0036] (1) The present invention provides a hydrogel thin layer-foam-based solar evaporator, comprising a foam substrate, a photothermal layer and a hydrogel thin layer; the photothermal layer and the hydrogel thin layer are sequentially coated on the foam substrate, or the photothermal layer, the hydrogel thin layer and the photothermal layer are sequentially coated on the foam substrate. Among them, the photothermal layer is a carbon-based indium material, which has a unique photothermal conversion ability, providing the possibility for efficient evaporation. The hydrogel thin layer composed of carbon-based indium material, polyvinyl alcohol and glutaraldehyde is further combined, so that the overall excellent hydrophilicity of the evaporator can achieve ideal water transport, reduce the binding energy of water molecules, and significantly reduce the evaporation enthalpy. With these characteristics, under the irradiation of 1 sun, the FCH evaporation rate and energy efficiency are 7.93kgm -2 h -1 and 315%; the hydrogel layer in FCH absorbs sunlight and converts it into heat, and then gradually heats the water in the thin layer. The presence of intermediate water (IW) inside the hydrogel thin layer can reduce the energy required for evaporation and shorten the evaporation route. Liquid water is directly vaporized through IW to generate water vapor, ultimately achieving a higher evaporation rate.
[0037] (2) The present invention quickly prepares a foam-based evaporator loaded with a thin layer of hydrogel through a simple spraying method. The preparation process is simple and has universal applicability.
[0038] (3) The hydrogel thin layer-foam-based solar evaporator prepared by the present invention has a high evaporation rate and energy utilization efficiency, and also exhibits excellent salt tolerance in 3.5-20wt.% salt water, and also has a high evaporation rate in acid, alkali and various dye wastewaters. It has a wider application in seawater desalination, high-salt wastewater, acid, alkali and various dye wastewater treatment, which exceeds most existing evaporators. The foam-based evaporator has a large-scale application potential due to its stable evaporation performance under various conditions, providing a reliable path for actual freshwater production. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0040] Figure 1 The SEM images of the foam and FCH in the non-compression direction and the compression direction in Example 1 of the present invention at different magnifications; wherein, (a) and (b) are foams in the non-compression direction, with magnifications of 50 and 200, respectively; (c) and (d) are foams in the compression direction, with magnifications of 100 and 500, respectively; (e) and (f) are FCH in the non-compression direction, with magnifications of 50 and 200, respectively; (g) and (h) are FCH in the compression direction, with magnifications of 100 and 500, respectively;
[0041] Figure 2 FT-IR spectra of C-5, PVA and FCH in Example 1 of the present invention;
[0042] Figure 3 is the X-ray diffraction pattern of C-5, PVA and FCH in Example 1 of the present invention;
[0043] Figure 4 This is the water contact angle test of Foam, FC, FCH and FCHC in Example 1 of the present invention;
[0044] Figure 5 DSC curves of pure water, FC, FCH and FCHC in Example 1 of the present invention;
[0045] Figure 6 The stability of FCH in Example 1 of the present invention in a pH=1 HCl solution, a pH=13 NaOH solution, ethanol and acetone after ultrasonic treatment for 1 hour;
[0046] Figure 7 is the evaporation rate of different photothermal materials in Example 3 of the present invention and Comparative Example 1; wherein BC is carbonized 1,3,5-benzenetricarboxylic acid;
[0047] Figure 8This is a schematic diagram of the solar evaporation simulation evaporation system in Application Example 1 of the present invention. DETAILED DESCRIPTION
[0048] Unless otherwise specified, the present invention has no special requirements on the sources of the raw materials used, and commercially available products known to those skilled in the art may be used.
[0049] Name explanation:
[0050] Foam evaporator: foam evaporator;
[0051] FC evaporator: “foam + photothermal layer” evaporator;
[0052] FCH evaporator: “foam + photothermal layer + hydrogel thin layer” evaporator;
[0053] FCHC evaporator: “foam + photothermal layer + hydrogel thin layer + photothermal layer” evaporator.
[0054] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0055] Example 1
[0056] 1. Preparation of carbon-based indium material (C-5)
[0057] The precursor of C-5 material was prepared by hydrothermal method. First, 3g of trimesic acid was weighed and added to 96mL DMF (N,N-dimethylformamide) to dissolve as solution A, and 0.6g In(NO3)3 was added to 24mL methanol to dissolve as solution B. Then, solution A was added to solution B, and the mixture was stirred and dissolved for 30min. Subsequently, the mixture was transferred to a reactor and reacted at 120℃ for 24h to obtain a precipitate. Then, it was washed with methanol and centrifuged, and the obtained sample was vacuum dried for use. Subsequently, the sample was calcined at 500℃ in a tubular furnace for 2h in a nitrogen atmosphere, and the target material C-5 was obtained after cooling.
[0058] 2. Preparation of solar evaporator
[0059] (1) A piece of melamine foam with the dimensions of 8 cm (length) × 4 cm (width) × 0.5 cm (thickness) was used as the substrate. It was washed with water and ethanol several times to remove dust and grease on the surface and then dried in an oven at 60°C.
[0060] (2) Pure foam is assembled into a Foam evaporator. Assembly is the process of transforming a flat foam into a 3D evaporator, and assembling a 8cm×4cm×0.5cm flat melamine foam into a 2cm×2cm×0.5cm three-dimensional evaporator.
[0061] (3) Preparation concentration is 0.1 g / mL -1 The C-5 aqueous solution is sprayed on the inner and outer surfaces of the foam substrate with a spray gun and then assembled into an FC evaporator; wherein, the C-5 aqueous solution is quantitatively sprayed in a quantity of 3 mL.
[0062] (4) Disperse C-5 in a 12.5 wt.% polyvinyl alcohol (PVA) solution to form solution C, in which the concentration of C-5 is 0.1 g / mL. Solution C is first sprayed on the inner and outer surfaces of the foam substrate, and then a layer of glutaraldehyde (GA) is sprayed on the inner and outer surfaces of the foam substrate for cross-linking, and finally assembled to form an FCH evaporator containing a thin layer of hydrogel. The spraying amount of solution C is 3 mL, and the spraying amount of glutaraldehyde is 0.3 mL. The ratio of the amount of solution C to GA is 10:1. Figure 1 As shown in (h), the thickness of the hydrogel layer is 300-350 μm.
[0063] (5) Spray another layer of 1 mL of 0.1 g mL on the inner and outer surfaces of FCH. -1 The FCHC evaporator can be obtained by adding the C-5 dispersion. All evaporators have a height of 4 cm.
[0064] In the wavelength range of 200-2500nm, the FC evaporator achieved 74.65% light absorption, the FCH evaporator achieved 91.97% light absorption, and the FCHC evaporator achieved 94.68 light absorption. The hydrogel thin layer and C-5 work together to increase the surface roughness and induce multiple reflections in the light path, thereby increasing light absorption.
[0065] Figure 2 FT-IR spectra of C-5, PVA and FCH in Example 1.
[0066] Figure 3 1 is the X-ray diffraction pattern of C-5, PVA and FCH in Example 1.
[0067] Figure 4 This is the water contact angle test of Foam, FC, FCH, and FCHC in Example 1. The water contact angle test shows that once a water drop contacts the surface of Foam, FC, FCH, and FCHC, the droplet collapses quickly when it drops directly on the surface and immediately penetrates into the body.
[0068] Figure 5 The DSC curves of pure water, FC, FCH and FCHC in Example 1. The evaporation enthalpy values of FCH and FCHC are much lower than that of pure water, which proves that the presence of the hydrogel layer weakens the hydrogen bond interaction and requires less energy to complete the evaporation of water.
[0069] Figure 6The stability of FCH in Example 1 after ultrasonic treatment for 1 h in pH=1 HCl solution, pH=13 NaOH solution, ethanol and acetone proves the stability of the coating.
[0070] Example 2
[0071] Different from Example 1, the preparation of the solar evaporator does not include steps (4) and (5). The FC evaporator prepared in this example is.
[0072] Example 3
[0073] Different from Example 1, the preparation of the solar evaporator does not include step (5). The FCH evaporator prepared in this example is.
[0074] Example 4
[0075] Different from Example 1, in the preparation process of the solar evaporator, in step (4), the spraying amount of solution C is 4 mL, and the spraying amount of glutaraldehyde is 0.4 mL.
[0076] Comparative Example 1
[0077] Different photothermal materials
[0078] The difference from Example 3 is that C-5 in Example 3 is replaced with carbon powder, carbon powder + In(NO3)3, BC or B-C + In(NO3)3. Among them, BC is carbonized 1,3,5-benzenetricarboxylic acid, and the evaporation rate is lower than that of FCH evaporator. For specific evaporation rate, see Figure 7 .
[0079] Application Example 1
[0080] Indoor solar evaporation experiment:
[0081] like Figure 8 As shown, a xenon lamp is set on the top of the sample as the incident light source, and the output solar light intensity is 1kWm -2 The light intensity is monitored by an optical power meter, and the temperature change of the sample surface is measured by an infrared thermal imager. At room temperature (28°C, humidity about 50%), the evaporators prepared in Examples 1, 2, and 3 are placed in a beaker filled with water, so that the entire evaporator floats on the water surface to facilitate water replenishment. The beaker is then placed on an analytical balance (measurement accuracy 0.0001g) connected to a computer, and the change in the balance mass is recorded in real time to evaluate the water evaporation performance of the evaporator under simulated sunlight. Each sample is tested five times and the average value is taken. Figure 8 shown.
[0082] Under 1 sun irradiation, the evaporation rate and energy efficiency of the FC evaporator are 4.90 kgm -2 h -1and 237%, the evaporation rate and energy efficiency of the FCH evaporator were 7.93kgm -2 h -1 and 315%, the evaporation rate and energy efficiency of the FCHC evaporator are 6.05kgm -2 h -1 and 284%. Compared with FC and FCHC evaporators, FCH evaporator has better water evaporation rate and energy efficiency.
[0083] The hydrogel layer in FCH absorbs sunlight and converts it into heat, and then gradually heats the water in the layer. The presence of IW inside the hydrogel layer can reduce the energy required for evaporation and shorten the evaporation route. Liquid water is directly vaporized through IW to generate water vapor, ultimately achieving a higher evaporation rate.
[0084] Application Example 2
[0085] Evaporation performance experiment of evaporator at salt component content (3.5-20wt.%):
[0086] Different from Application Example 1, the FCH evaporator prepared in Example 3 was placed in a beaker filled with NaCl.
[0087] In 3.5wt.% NaCl solution, under 1 sun irradiation, the evaporation rate of FCH is 7.59kgm -2 h -1 , the energy efficiency is 300%, which is similar to the evaporation effect in pure water. As the salt concentration increases from 3.5-20wt.%, the evaporation rate and energy efficiency gradually decrease, but even in 20wt.% NaCl solution, it reaches 5.55kgm -2 h -1 evaporation rate and 217% energy efficiency.
[0088] Application Example 3
[0089] Application of evaporator in evaporation of acid and alkaline water:
[0090] Different from Application Example 1, the FCH evaporator prepared in Example 3 is placed in acid and alkali solutions respectively.
[0091] When the acid solution is 0.1 mol / L hydrochloric acid with a pH of 1, the evaporation rate of FCH is 6.74 kg / m -2 h -1 , energy efficiency is 266%.
[0092] When the alkaline solution is 0.1 mol / L sodium hydroxide with a pH of 13, the evaporation rate of FCH is 6.51 kg / m -2 h -1 , the energy efficiency is 256%.
[0093] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A hydrogel thin layer-foam-based solar evaporator, characterized in that: It comprises a foam substrate, a photothermal layer and a hydrogel thin layer; the photothermal layer and the hydrogel thin layer are sequentially coated on the foam substrate; Among them, the photothermal layer is a carbon-based indium material; The hydrogel layer includes a carbon-based indium material, polyvinyl alcohol and glutaraldehyde; The carbon-based indium material is prepared by mixing an indium nitrate solution and a trimesic acid solution, preparing a precursor by a hydrothermal method, and calcining the precursor under a protective atmosphere; The calcination temperature is 450-550°C and the calcination time is 1-3h.
2. The hydrogel thin layer-foam-based solar evaporator according to claim 1, characterized in that: The method also includes coating a photothermal layer on the hydrogel thin layer.
3. The hydrogel thin layer-foam-based solar evaporator according to claim 1 or 2, characterized in that: The foam substrate is melamine foam or polyurethane foam.
4. The method for preparing a hydrogel thin layer-foam-based solar evaporator according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Assembling the foam base into a foam evaporator; (2) coating the carbon-based indium material aqueous solution on the inner and outer surfaces of the foam substrate to obtain an FC evaporator; (3) A carbon-based indium material and polyvinyl alcohol are mixed to form a solution C. The solution C and glutaraldehyde are coated on the inner and outer surfaces of the foam substrate in sequence to obtain a FCH evaporator.
5. The preparation method according to claim 4, characterized in that: The method also includes step (4), coating the inner and outer surfaces of the FCH evaporator with an aqueous solution of a carbon-based indium material to obtain a FCHC evaporator.
6. The preparation method according to claim 4, characterized in that: Before step (1), the method further includes washing and drying the foam substrate; In step (1), the foam substrate is melamine foam or polyurethane foam.
7. The preparation method according to claim 5, characterized in that: In step (2), the concentration of the carbon-based indium material aqueous solution is 0.05-1 g / mL; In step (3), the concentration of the carbon-based indium material in solution C is 0.05-1 g / mL; The mass fraction of the polyvinyl alcohol is 10-15wt.%; During coating, the volume ratio of solution C and glutaraldehyde is (9-10):1; In step (4), the concentration of the carbon-based indium material aqueous solution is 0.05-1 g / mL; The volume ratio of the coating amount of the carbon-based indium material aqueous solution in step (2), the coating amount of solution C in step (3), and the coating amount of the carbon-based indium material aqueous solution in step (4) is (1-5):(1-5):(1-3).
8. The preparation method according to claim 4, characterized in that: The preparation method of the carbon-based indium material comprises: mixing an indium nitrate solution and a trimesic acid solution, preparing a precursor by a hydrothermal method, and calcining the precursor under a protective atmosphere to obtain the carbon-based indium material; Wherein, the mass ratio of indium nitrate to trimesic acid is 1:(5-10); The calcination temperature is 450-550°C and the calcination time is 1-3h.
9. Application of a hydrogel thin layer-foam-based solar evaporator in seawater desalination, high-salinity wastewater, acid-base and various dye wastewater treatment, wherein: The hydrogel thin layer-foam-based solar evaporator is the hydrogel thin layer-foam-based solar evaporator described in any one of claims 1 to 3, or is the hydrogel thin layer-foam-based solar evaporator obtained by the preparation method described in any one of claims 4 to 8.
Citation Information
Patent Citations
Preparation method and application of mesoporous metal-organic framework material with high stability
CN103864607A
Preparation method of seawater desalination material based on polyurethane foam
CN110511558A
Phototropic solar photo-thermal seawater evaporation method and phototropic solar photo-thermal seawater evaporation device
CN111348708A
Photo-thermal evaporation material derived on basis of iron-based metal organic framework and preparation method and application of photo-thermal evaporation material
CN118420850A